2012
DOI: 10.1177/0884533611431462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Roux‐en‐Y Gastric Bypass Surgery on Vitamin C, Myeloperoxidase, and Oral Clinical Manifestations

Abstract: Background Bariatric surgery influences the intake and absorption of nutrients, which, when associated with vomiting, can damage the oral cavity. The serum concentrations of vitamin C and myeloperoxidase (MPO) and oral clinical manifestations were examined in patients 2 years after Roux‐en‐Y gastric bypass (RYGB). Methods Clinical prospective study with control group (CG; n = 26), assessed only once, and the bariatric group (BG; n = 26), assessed in the basal period and at 12 and 24 months after surgery. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Sales‐Peres et al () evaluated if periodontal disease and periopathogens were influenced by gastric bypass operation, and their findings showed an increased periodontal disease in the study group. This was in accordance with the findings of Marsicano et al () and Netto et al (), where a small difference in increased dental pocket depth in individuals that have undergone bariatric surgery was demonstrated, compared with obese patients who had not undergone bariatric surgery. Netto et al () also reported that vitamin C deficiency and increased vomiting after surgery might be an explanation to increased periodontal disease postoperative in the study group.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Sales‐Peres et al () evaluated if periodontal disease and periopathogens were influenced by gastric bypass operation, and their findings showed an increased periodontal disease in the study group. This was in accordance with the findings of Marsicano et al () and Netto et al (), where a small difference in increased dental pocket depth in individuals that have undergone bariatric surgery was demonstrated, compared with obese patients who had not undergone bariatric surgery. Netto et al () also reported that vitamin C deficiency and increased vomiting after surgery might be an explanation to increased periodontal disease postoperative in the study group.…”
Section: Introductionsupporting
confidence: 93%
“…This was in accordance with the findings of Marsicano et al () and Netto et al (), where a small difference in increased dental pocket depth in individuals that have undergone bariatric surgery was demonstrated, compared with obese patients who had not undergone bariatric surgery. Netto et al () also reported that vitamin C deficiency and increased vomiting after surgery might be an explanation to increased periodontal disease postoperative in the study group. A cohort study (de Moura‐Grec et al, ) evaluated oral health conditions before and 6 months after bariatric surgery, and the results showed that systemic conditions could improve but oral health conditions deteriorated because of increased periodontal disease and decayed teeth.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In one study postoperative gastric bypass patients given 100 mg FeSO 4 tablets as an oral challenge absorbed inadequate amounts of iron as measured by change in serum iron concentration [44]; altered gut physiology after bariatric surgery may not allow for iron absorption from FeSO 4 tablets. Furthermore, several studies have also documented low vitamin C levels in patients after bypass procedures [45,46], therefore liquid iron preparations with added ascorbate -such as Spatone Apple ® and Iron Vital F ® (which also has other micronutrients) -may be helpful in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a significant reduction in serum vitamin C after 24 months after Roux-en-Y BS has been described [77]. Nevertheless other authors have not reported such a deficiency, so it remains controversial [33].…”
Section: Discussionmentioning
confidence: 99%